2023
DOI: 10.5435/jaaos-d-22-01026
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy in Orthopaedics

Abstract: Health literacy is a dynamic, multifaceted skill set that relies on patients, healthcare providers, and the healthcare system. In addition, health literacy assessment provides an avenue for evaluating patient understanding and offers insights into their health management capabilities. Inadequate health literacy results in poor patient outcomes and compromised care by considerably hindering successful communication and comprehension of relevant health information between the patient and the provider. In this na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The World Health Organization identifies health literacy levels as one of the major determinants of societal health and considers health literacy vital for empowerment [ 4 ]. Limited health literacy is associated with adverse health outcomes [ 5 ]. Many unfavorable outcomes in disease management and accidents result from insufficient health literacy among individuals and families [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization identifies health literacy levels as one of the major determinants of societal health and considers health literacy vital for empowerment [ 4 ]. Limited health literacy is associated with adverse health outcomes [ 5 ]. Many unfavorable outcomes in disease management and accidents result from insufficient health literacy among individuals and families [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the interpretation of PROMs is predicated upon a patient's understanding of questionnaires to accurately represent their progression after spine disease diagnosis and surgery. 3 Poor patient understanding of health care information contributes to significant disparities in access to care and outcomes after surgery. In the United States, a 2003 national assessment on health literacy demonstrated that only 12% of adults have the necessary health literacy to manage their own care.…”
mentioning
confidence: 99%
“…PROMs, therefore, become critical in assigning quantifiable value to an inherently subjective measure. However, the interpretation of PROMs is predicated upon a patient's understanding of questionnaires to accurately represent their progression after spine disease diagnosis and surgery 3 …”
mentioning
confidence: 99%